Amsterdam as a sustainable European metropolis: integration of water, energy and material flows. Issue 1 (2nd January 2017) - van der Hoek, J.P.; Struker, A.; de Danschutter, J.E.M.
Abstract : ABTRACT: Amsterdam has the ambition to develop as a competitive and sustainable European metropolis. The flows of energy, water and resources within the urban environment have a large potential to contribute to this ambition. Through a transition from a linear usage of resources and waste production towards a sustainable management of urban resources with circular flows of resources, the sustainability of cities can be increased. This Urban Harvesting Concept may be applied in Amsterdam. The challenge is how to operationalize this concept in practice. For two municipal companies in Amsterdam, Waternet (responsible for the water management) and AEB (the waste-to-energy company), initiatives were identified on how to do this. The focus is on water, energy, waste and material flows. Circular flows result in economic benefits and sustainability benefits, either expressed as Ecopoints or CO2 -emissions. The integration of these flows is especially beneficial.